The subgenus Astomyrme Schwartz, 1984 in the Iberian Peninsula: associating Physetopoda pusilla (Klug in Waltl, 1835) with Smicromyrme suberratus Invrea, 1957, and description of the hitherto unknown female of S. matritentis (Mercet, 1905) (Hymenoptera: Mutillidae) - Matias, Rafael (Zootaxa, 2024)
The sexually dimorphic mutillid wasps (Hymenoptera: Mutillidae) are generally poorly known insects; in the Iberian Peninsula several common and widespread species are known from only one sex, for which sex-associations still need to be established. Such is the case with Smicromyrme (Astomyrme) suberratus Invrea, 1957, known only from males, and Physetopoda pusilla (Klug in Waltl, 1835), known from females. In this paper, making use of conclusive sex-association experiments and other elements, S. suberratus and P. pusilla are discovered to be opposite sexes of the same species, nearly 200 years after the female holotype was collected; female (including holotype) and male are redescribed, complemented with an illustrated account of their intraspecific variation. New combination and new synonymy are proposed for Smicromyrme (Astomyrme) pusillus (Klug in Waltl, 1835), comb. nov. (=Mutilla subcomata Radoszkowski, 1888, syn. nov. and =Smicromyrme suberrata Invrea, 1957, syn. nov.). The geographical distribution of the male sex (mostly western Mediterranean), suggests the female of a similar, cryptic species, may represent the records of P. pusilla in eastern areas, where the male (i.e. S. suberratus) is currently unknown. The Iberian endemic Smicromyrme matritensis (Mercet, 1905) is newly found in Portugal, its hitherto unknown female is described, and the male redescribed. Structural features of both males and females place these two species unequivocally in the subgenus Astomyrme Schwartz, 1984; diagnostic features of Astomyrme females are discussed. Notes are presented regarding a third Iberian Astomyrme, S. (A.) opistomelas Invrea, 1950. An updated key to the Smicromyrme Thomson, 1870 of the Iberian Peninsula is included.